2002
DOI: 10.1007/s00464-001-8191-x
|View full text |Cite
|
Sign up to set email alerts
|

A combination of heparin and an intermittent pneumatic compression device may be more effective to prevent deep-vein thrombosis in the lower extremities after laparoscopic cholecystectomy

Abstract: A combination of low-molecular-weight heparin and intermittent pneumatic compression may be more effective to prevent deep-vein thrombosis in the legs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…There have been studies advocating both mechanical and pharmacological DVT prophylaxis ( London: Royal College of Physicians, 2010 ; Okuda et al, 2002 ), but there have also been other studies suggesting that prophylaxis during LCs is unnecessary ( Agnelli, 2004 ; Blake, Toker & Dunn, 2001 ; Lindberg, Bergqvist & Rasmussen, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies advocating both mechanical and pharmacological DVT prophylaxis ( London: Royal College of Physicians, 2010 ; Okuda et al, 2002 ), but there have also been other studies suggesting that prophylaxis during LCs is unnecessary ( Agnelli, 2004 ; Blake, Toker & Dunn, 2001 ; Lindberg, Bergqvist & Rasmussen, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal insufflation and the reverse Trendelenburg position of the patient were shown to enhance venous stasis in the lower limbs [4]. Moreover, hypercoagulability and damage to the vessel may also occur [5–7]. However, despite the potential for the development of DVT our findings suggest that this complication is rare.…”
Section: Discussionmentioning
confidence: 90%
“…Jacobs et al (12) reported that sequential gradient intermittent pneumatic compression induced prompt, but short-lived, alterations in fibrinolytic function, and the values quickly reverted to baseline on the termination of compression. Okuda et al (8) reported that the intermittent compression boot did not prevent increased intravascular thrombogenesis and platelet activation through significant increases of plasma Ddimer and β-thromboglobulin after laparoscopic cholecystectomy. Killewich et al (10) also reported that enhanced regional fibrinolysis in the lower extremities could not be detected with the use of external pneumatic compression devices, as measured with the tissue plasminogen activator and plasminogen activator inhibitor-1 activity in common femoral venous blood samples obtained from patients undergoing abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Stasis alone does not cause thrombosis, but the combination of stasis, hypercoagulability, and endothelial damage allows thrombus to develop (2). Some studies demonstrated (3)(4)(5)(6)(7)(8) that laparoscopic cholecystectomy leads to postoperative activation of the coagulation system, which is one of the factors for postoperative thromboembolic complications. These changes can also be present in laparoscopic fundoplications.…”
Section: Introductionmentioning
confidence: 99%